How do we restore New Zealand's biological heritage by 2050?. (27th September 2016) - Norton, David A.; Young, Laura M.; Byrom, Andrea E.; Clarkson, Bruce D.; Lyver, Phil O'B.; McGlone, Matt S.; Waipara, Nick W.
Abstract : If we are to make meaningful and measurable progress in restoring New Zealand's biological heritage by 2050, a range of fundamental issues need to be addressed. These relate not just to restoration science but also to building ecosystem resilience in the wider socio‐economic and cultural context within which restoration occurs.